KEWAJIBAN PENGUSAHA PD TITIK GENSET TERHADAP KONSUMEN DALAM PERJANJIAN TUKAR MENUKAR PERALATAN RUMAH TANGGA DI KELURAHAN SAIGON KECAMATAN PONTIANAK TIMUR - NIM. A1011161235, WILINDA SARI (Fakultas Hukum Universitas Tanjungpura, 2025)
Abstract Household Equipment Exchange Agreement between the Buyer and PD. Gensets are carried out through advertisements on social media, especially regarding price benchmarks in all conditions. However, in practice, the benchmark price offered to buyers changed to a low price value that was not in accordance with the agreement advertised via social media. so that the Buyer suffers a loss. For this reason, the author tries to write it in the form of a thesis with the title: